Determining the Effect of Bar Model Technique on Students’ Mathematical Word Problem Solving Skills - Muhammad Naeem Shah, (JCTE, 2023)
The study aims at probing the effect of Bar Model Technique on the word problem solving skills of primary level students in the subject of mathematics. Following were the objectives (i) to determine the effect of Bar Model Technique on student’s mathematical word problem solving skills; (ii) to compare the academic achievements of male students and female students by using Bar Model Technique. It was experimental study and pretest-posttest equivalent group design was used as a tool for data collection in this study. Sample of the study was 40 students (Male & Female) of Government Primary School District Nowshera, Khyber Pakhtunkhwa. The sample students were divided in two group control and experimental on the base of pretest score by using paired random technique. Data were analyzed by mean, SD and t- test.